Tingkat pemahaman siswa terhadap teks wacana dalam aspek tema dan struktur pada program GLS di sekolah dasar - Muhammad Sholihul Huda; Karsono Karsono; Matsuri Matsuri (Universitas Sebelas Maret, 2024)
Understanding the content of reading texts is one of the language skills included in reading skills. This study aims to describe the level of ability of fourth grade students in understanding the content of reading texts in the School Literacy Movement program, which was developed by focusing on aspects of the theme and structure of the discourse text. This research is a mix method study. The subjects in this research were fourth grade students and fourth grade teachers at Soropadan Elementary School. Data collection used in this research was tests, interviews with class IV teachers, and document studies. The data analysis technique in this research uses the Miles and Huberman model of interactive data analysis techniques. Data validity testing techniques use triangulation of sources and techniques. Data presentation uses simple descriptive statistics. The results of this study indicate that the percentage obtained in the aspect of identifying the reading theme is 83.92% and 86.60% in the aspect of identifying the reading structure. From the results of the study, it can be concluded that the level of students' understanding of the contents of the reading in the School Literacy Movement program at Soropadan Elementary School is already in the good category. This condition occurs as a result of the activity pattern of the School Literacy Movement at Soropadan Elementary School which has been taking place regularly and continuously.